Postpartum depression literacy in Chinese perinatal women: a cross-sectional study - Huang, Weijian; Li, Guiqin; Wang, Dongmei; Qu, Hua; Tian, Maozhou; Wang, Yanmei (Frontiers in Psychiatry, 2023)
Background: Postpartum depression literacy is a specific mental health literacy that can help perinatal women identify, manage, and prevent postpartum depression. However, the current status and associated factors of postpartum depression literacy among Chinese perinatal women are still unclear. This study investigated postpartum depression literacy and its associated factors among this group. Methods: A cross-sectional survey was conducted involving 386 cases of perinatal women using the convenience sampling method. Participants completed four questionnaires to evaluate their general characteristics, postpartum depression literacy, perceived social support, and general self-efficacy. The SPSS 24.0 software was used for descriptive statistical analysis, univariate analysis, and multivariate analysis. Results: The total PoDLiS score was (3.56 ± 0.32). The factors that composed the final multiple regression equation included planned pregnancy condition (β = -0.137, p = 0.003), education (β = 0.127, p < 0.001), history of depression (β = -0.271, p < 0.001), social support (β = 0.0012, p < 0.001), self-efficacy (β = 0.030, p < 0.001), and complications (β = -0.0191, p = 0.0019). They accounted for 32.8% of the total postpartum depression literacy variation (R2 = 0.328, F = 24.518, p < 0.001). Conclusion: The findings of this study improved our understanding of perinatal women’s postpartum depression literacy and its associated factors. Women with low postpartum depression literacy urgently need to be identified. Comprehensive nursing intervention measures should be taken from six dimensions of mental health literacy, social support, and self-efficacy to improve the postpartum depression literacy of perinatal women.